Consumo de antidepressivos em adultos usuários da Atenção Primária do Sistema Único de Saúde - Natália Patrícia Batista Torres (2020)
The aim of this study was to estimate the prevalence of antidepressant use in the last 30 days in adult primary care users of the Brazilian National Health System. Additionally, we investigated the association between antidepressant use and selected characteristics. This work is part of the National Survey on Access, Use and Promotion of the Rational Use of Medicines in Brazil - Services, a cross-sectional, evaluative and exploratory study conducted through questionnaires applied to basic health units and medicine dispensing services. We conducted 8.803 interviews in the five Brazilian regions from July to December 2014. The response variable was the use of antidepressants. We performed a descriptive analysis of the population studied and the antidepressants. We measured the association between antidepressant use and demographic, socioeconomic, clinical and lifestyle-related variables through logistic regression. The prevalence of antidepressant use was 6.8% (95% CI 6.2 - 7.3). Among users who self-reported a previous diagnosis of depression and being extremely depressed / anxious, only 29.4 and 24.4%, respectively, reported using antidepressants, suggesting a probable underuse. The most used drugs were fluoxetine (37.9%), amitriptyline (26.1%) and sertraline (10.1%). After all adjustments, multivariate analysis found that the use of antidepressants is more likely in females, aged between 18 and 44 years, higher socioeconomic status, white ethnicity/race, who self-reported depression and anxiety / depressive status, polypharmacy and use of psychotropic, who were not hospitalized in the previous year and alcohol abstinent. The prevalence of antidepressant use observed is lower than in USA and some European countries but is consistent with other studies conducted in Brazil. The factors associated with its use are consistent with the literature.The findings suggest that there may be inequity in access to drug treatment for depression in the Brazilian National Health System. Although patients have a universal right to health in Brazil, the inequities found, especially for non-white individuals and those from lower social classes, show that it is necessary to improve actions to ensure access to treatment of depressive disorders by primary care users.